Gleisanschlusslogistik. Bewertung künftiger Entwicklung auf Grund der Gleisanschlussförderrichtlinie. - Häßler, Michael; Hildebrand, Wolf-Christian (Deutscher Verkehrs-Verl., 2007)
Die Güterverkehrsleistung in Deutschland ist in den vergangenen Jahrzehnten kontinuierlich angestiegen. Das Wachstum fiel dabei insbesondere zu Gunsten des Straßengüterverkehrs aus, wenn auch in einer europäischen Betrachtung die Güterverkehrsleistung in Deutschland auf der Schiene und in der Binnenschifffahrt höhere Anteile zu verzeichnen hatte als im EU-Durchschnitt. difu

Railway sidings are of special importance for the rail cargo. Up to 90 per cent of the rail cargo is handled via railway sidings in Germany. Therefore, railway sidings are important infrastructural elements for rail freight transport as well as for sustainable supply chains. Due to the increased complexity of logistical chains and processes as well as due to global procurement, production, and distribution there is, again, interest in rail cargo and railway sidings to be seen. However, railway systems are more cost intensive than roads. Therefore, the federal ministry of traffic, building, and housing legislated instruction to financially support railway sidings in September 2004. Within the paper the authors have a closer look at three issues concerning railway sidings. difu
Keywords: Verkehr; Güterverkehr; Straßengüterverkehr; Schienengüterverkehr; Verkehrspolitik; Förderungsprogramm; Verkehrsleistung; Gleisanschlussförderrichtlinie; Richtlinie; Verkehrsverlagerung; Gleisanschluss; Schieneninfrastruktur